STEM-14. THE WRAD COMPLEX REPRESENTS A THERAPEUTIC TARGET FOR CANCER STEM CELLS IN GLIOBLASTOMA. (12th November 2021) - Mitchell, Kelly; Alvarado, Joseph; Goins, Christopher; Martinez, Steven; Macdonald, Jonathan; Silver, Daniel J; Roversi, Gustavo; Kay, Kristen; Schafer, Rachel; Kashyap, Anjali; Lauko, Adam; Mulkearns-Hubert, Erin E; et al.
Abstract: Glioblastoma (GBM) progression and resistance to conventional therapies is driven in part by cells within the tumor with stem cell properties including quiescence, self-renewal and drug efflux potential. It is thought that eliminating these cancer stem cells (CSCs) is a key component to successful clinical management of GBM. However, currently, few known molecular mechanisms driving CSCs can be exploited for therapeutic development. Core transcription factors such as SOX2, OLIG2, OCT4 and NANOG maintain the CSC state in GBM. Our laboratory recently uncovered a self-renewal signaling axis involving RBBP5 that is necessary and sufficient for CSC maintenance through driving expression of these core stem cell maintenance transcription factors. RBBP5 is a component of the WRAD complex, which promotes Lys4 methylation of histone H3 to positively regulate transcription. We hypothesized that targeting RBBP5 could be a means to disrupt epigenetic programs that maintain CSCs in stemness transcriptional states. We found that genetic and pharmacologic inhibition of the WRAD complex reduced CSC growth, self-renewal and tumor initiation potential. WRAD inhibitors partially dissembled the WRAD complex and reduced H3K4 trimethylation both globally and at the promoters of key stem cell maintenance transcription factors. Using a CSC reporter system, we demonstrated that WRAD complex inhibition decreased growth of SOX2/OCT4 expressing CSCs in a concentration-dependent manner as quantified by live imaging. Overall, our studies assess the function of the WRAD complex and the effect of WRAD complex inhibitors in preclinical models and specifically on the stem cell state for the first time in GBM. Studying the functions of the WRAD complex in CSCs may improve understanding of GBM pathogenesis and elucidate how CSCs survive despite aggressive chemotherapy and radiation. Our ongoing studies aim to develop brain penetrant inhibitors targeting the WRAD complex as an anti-CSC strategy that could potentially synergize with standard of care treatments.